The width of edge effects of road construction on fauna and ecologically critical road density - Lin, Shyh-Chyang (Journal of Environmental Engineering and Landscape Management, 2015)
This study investigates the ecological impacts of road construction by trapping rodents, invertebrates, and amphibians with wire-mesh traps and pitfalls along a road under construction on Kinmen island, Taiwan. The capture data show that the Brown country rat’s (Rattus losea) edge habitat is broader in woodland habitat next to farmland than it is in woodland next to the road. Similarly, most invertebrates captured were found within the woodland at an edge width of 15 m along the roadside and 35 m along the farmland. On the other hand, the Ornate rice frog (Microhyla ornate), which typically resides and forages in dim and humid environments, avoids edges. The edge effect results in this paper are applied in a model for determining ecologically critical road density. The estimation of edge width and critical road density obtained in this study can be applied during road planning and design to assess the potential effects of habitat conversion during road construction. First published online: 19 Oct 2015